Analisis Sistem Kinerja PLC Pada Air Dryer di Unit Utilities PT. X - Hengkesa, Melinda; Dewi, Astrie Kusuma (Elposys: Jurnal Sistem Kelistrikan, 2024)
The refinery process in PT. X relies on several supporting units, including the air dryer in the utilities section, which is essential for removing water content from compressed air to support refinery operations. This research aimed to analyze the performance of the Programmable Logic Controller (PLC) system in the air dryer units (A, B, C, and D), each comprising two towers that can operate alternately or simultaneously. The conventional TM series controller was replaced with a Schneider Electric Modicon M340 PLC to enhance system reliability and digitization. A methodical approach was adopted, beginning with data collection from sensors connected to the PLC, followed by processing the data using predefined logic instructions. The research findings indicated significant improvements in operational efficiency, response time, and energy consumption with the PLC system compared to the TM series. The PLC system also facilitated continuous and precise control of the drying and regeneration processes. These findings underscore the importance of adopting advanced PLC systems to ensure higher operational efficiency and reliability in industrial applications. Consequently, this research advocates for the comprehensive upgrade of conventional control systems to PLCs in similar industrial settings.